An intrinsically compliant robotic orthosis for treadmill training - Hussain, Shahid; Xie, Sheng Quan; Jamwal, Prashant K.; Parsons, John (Medical engineering & physics, 2012)
A new intrinsically compliant robotic orthosis powered by pneumatic muscle actuators (PMA) was developed for treadmill training of neurologically impaired subjects. The robotic orthosis has hip and knee sagittal plane rotations actuated by antagonistic configuration of PMA. The orthosis has passive mechanisms to allow vertical and lateral translations of the trunk and a passive hip abduction/adduction joint. A foot lifter having a passive spring mechanism was used to ensure sufficient foot clearance during swing phase. A trajectory tracking controller was implemented to evaluate the performance of the robotic orthosis on a healthy subject. The results show that the robotic orthosis is able to perform the treadmill training task by providing sufficient torques to achieve physiological gait patterns and a realistic stepping experience. The orthosis is a new addition to the rapidly advancing field of robotic orthoses for treadmill training.